HTTP blocking in RU: bbc.com, facebook.com, instagram.com, medium.com (Russia) - Voidly (Voidly Global Censorship Index, 2026)
WARNING severity censorship detected in Russia. Data sourced from CensoredPlanet.
Censorship Incident ID: RU-2026-0012. Severity: warning. Confidence: 85%